Global dynamics of solutions for a sixth-order parabolic equation describing continuum evolution of film-free surface - Duan, Ning; Zhao, Xiaopeng (Nonlinear Analysis: Modelling and Control, 2022)
This paper is concerned with a sixth-order diffusion equation, which describes continuum evolution of film-free surface. By using the regularity estimates for the semigroups, iteration technique and the classical existence theorem of global attractors we verified the existence of global attractor for this surface diffusion equation in the spaces H3(Ω) and fractional-order spaces Hk(Ω), where 0 ≤ k < ∞.